Cancer Incidence in the Syrian Coastal Zone in 2014 - عاقل, سامر (Latakia University Journal -Medical Sciences Series, 2021)
Scarce data are available about the incidence of cancer in Syria. We aim to report on the world age-standardized incidence rate (ASR-W) of all cancer types excluding non-melanoma skin cancer (NMSC) of the Syrian Coastal Zone (SCZ) and the five leading cancer sites for males and females in2014. Data was obtained from the Unite for Radio- and Chemotherapy of Tishreen University Hospital (URCTUH) in Latakia, which was the only cancer unite in the SCZ from 2006-2016. In this retrospective study, the new cancer patients who lived in SCZ and registered with the URCTUH log book were included. The Syrian Central Bureau of Statistics (CBSSYR) provided the demographic data based on the population survey conducted in 2014. Data of all Cancer types excl. NMSC were presented as incidence rates by age, gender, and the five leading cancer sites using ASR-W per 105 populations in SCZ. A total of 3073 new cases of cancer were registered in URCTUH-2014, 39 NMSC and 87 incomplete patient's medical files were excluded. 1375 of 2947 new Cancer exclude NMSC were living in SCZ (Males: n. 678, 49.31% and Females: n.697, 50.69%). ASR-W per 100.000/y in SCZ were 73.6 and 68.6, 71.6 in, males, females and both sexes respectively. The leading cancer sites in SCZ were: lung (n.137, 20.2%, ASR-W: 14.8), bladder (n.67, 9.9%, ASR-W:7.7), prostate (n.59, 8.7%, ASR-W: 7.2), colon (n.43, 6.3%, ASR-W:4.7) and larynx (n.41, 6%, ASR-W: 4.5) in males and breast (n.344, 49.4%, ASR-W: 32.6), ovary (n.40, 5.7%, ASR-W: 4.1), lung (n.22, 3.2%, ASR-W: 2.3), stomach (n.22, 3.2%, ASR-W:2.3), corpus Uteri (n.21, 3%, ASR-W: 2.2) in females. The largest proportion in men of all cancer sites, Lung, Bladder, Prostate, Colon and Larynx were in the age group 65 years and older. The largest proportion of all cancer sites, Ovary, Lung, Stomach and Corpus Uteri in females were also in the age group older than 65 years except in breast cancer where the incidence was mostly in age group between 40-54 years (51.5% of cases). This study has provided the latest evidence on the epidemiology of cancer in the SCZ of Syria that could be used to implement preventive measure and control interventions in a developing country.